Security and personal data protection in the European Union: challenging trends from a human rights’ perspective - Gonçalves, M. E. (2012)
The protection of personal data was first addressed in the EuropeanCommunity by Directive 95/46/CE. This Directive sought to reconcile personal data protection with the free movement of information in the Internal Market. The processing of personal data in the areas of security policy and police and judicial cooperation was excluded from the Directive‟s scope of application. However, in recent times, furthered by the “war on terror”, security policies have been reinforced in the European Union (EU), a key feature of these policies being the increased collection, use and exchange of information about individuals. Major electronic databases were set up. Additional measures such as the Data Retention Directive and agreements with the USA on Passenger Name Records (PNR) have also raised concerns about their bearing on fundamental rights and liberties. Remarkably though, the legal framework for the protection of personal data in the field of security is still recognisably unsatisfactory. This gap is currently in the process of being filled by way of legislative initiatives of the European Commission, submitted in January 2012. Nevertheless the question remains, how the balancing between security and the right to personal data protection is being construed by the EU. This issue was rendered more acute following the upgrading of personal data protection to the status of a fundamental right by the EU Charter of Fundamental Rights. In this paper, we will seek to address this topic based on a critical consideration of the evolution and current state of legal protection of personal data in the EU.